Traumatic injury results in prolonged circulation of ultralarge von Willebrand factor and a reduction in ADAMTS13 activity. Issue 6 (22nd May 2020) - Dyer, Mitchell R.; Plautz, William E.; Ragni, Margaret V.; Alexander, Wyeth; Haldeman, Shannon; Sperry, Jason L.; Guyette, Francis X.; Zuckerbraun, Brian S.; Rollins‐Raval, Marian A.; Raval, Jay S.; Neal, Matthew D.; ,
Abstract : BACKGROUND: Increases in plasma von Willebrand Factor (VWF) levels, accompanied by decreases in the metalloprotease ADAMTS13, have been demonstrated soon after traumatic injury while downstream effects remain unclear. STUDY DESIGN AND METHODS: A cohort of 37 injured trauma patients from a randomized control trial investigating the use of prehospital plasma transfusion were analyzed for activity and antigen levels of ADAMTS13 and VWF at 0 and 24 hours after admission. Relevant clinical data were abstracted from the medical records. Trauma patient plasma was analyzed via agarose gel electrophoresis to evaluate the effects of injury on VWF multimer composition compared to healthy controls. RESULTS: von Willebrand factor levels were elevated at presentation (189% [110%‐263%] vs. 95% [74%‐120%]), persisting through 24 hours (213% [146%‐257%] vs. 132% [57%‐160%]), compared to healthy controls. Ultralarge VWF (UL‐VWF) forms were elevated in trauma patients at both 0 and 24 hours, when compared to pooled normal plasma (10.0% [8.9%‐14.3%] and 11.3% [9.1%‐21.2%], respectively, vs. 0.6%). Circulating plasma ADAMTS13 activity was decreased at 0 hours (66% [47%‐86%] vs. 100% [98%‐100%]) and at 24 hours (72.5% [56%‐87.3%] vs. 103% [103%‐103%]) in trauma patients. ADAMTS13 activity independently predicted the development of coagulopathy and correlated with international normalized ratio, thromboelastography values, injury severity, and blood product transfusion. CONCLUSION: Traumatic injury is associated with acute coagulopathy that is characterized by increased UL‐VWF multimers and reduction in ADAMTS13, which correlates with blood loss, transfusion requirement, and injury severity. These findings suggest the potential for future trials targeting ADAMTS13 repletion to enhance clearance of VWF multimers.